Inovasi Kurikulum dan Pembelajaran Pada Masa Pandemi Covid-19 - Tatang Sudrajat; Omay Komarudin; Ni’mawati Ni’mawati; Qiqi Yuliati Zaqiah (Peneliti.net, 2020)
Covid-19 pandemic in the world including in Indonesia regarding government policies, including in that field in the education sector. Large-scale Social Restrictions (PSBB) in most regions in Indonesia are supported by the Government, in this case the Ministry of Education and Culture decides students to study at home with parental guidance. With this policy, teachers are required to be creative and innovative in working on the curriculum in accordance with the existing situations and needs. The research objective is to study curriculum and learning during the co-19 pandemic. This study uses a descriptive qualitative method that analyses and then clearly illustrates the problem sourced from a literature review. The results of this study are: 1) Curriculum innovation is an inevitability that cannot be accounted for, mostly for different discussions as currently in the Covid-19 pandemic. 2) Curriculum components are objectives, learning materials, learning processes, renewed search for help in the implementation is by utilizing the internet and TVRI.